How to achieve safe motherhood in Peru - Távara, Luis (2015)
Today, maternal perinatal health should be incorporated within the concept of Safe Motherhood and as such, an integral part of reproductive health. This is best understood as a right of individuals. Consequently, the provision of care for pregnant women and reduction of maternal and perinatal mortality should be viewed as an issue of human rights and social justice.